Typification of Nietneria corymbosa (Nartheciaceae), the type of the generic name - Silva, Diego Nunes Da; Fraga, Fernanda Ribeiro De Mello; Santana, Mariana Henriques (Phytotaxa, 2020)
Nietneria is the only neotropical genus of Nartheciaceae, represented by two species: N. corymbosa and N. paniculata. The collections of the brothers Moritz Richard and Robert Hermann Schomburgk in the Guiana Shield are the first records of special value for Botany, Zoology, and Mineralogy in this region. The brothers carried out an important set of botanical collections for the Guyana flora, in different periods and expeditions, which were organized in different series. Among these, the “Robert’s second collection series (Rob. ser. 2)”, corresponding to the period from 1841 to 1844, which resulted in the discovery of the genus Nietneria. In the present article, we provide a proper designation of a lectotype for Nietneria corymbosa, as a result of an ongoing monograph for the genus in Brazilian Flora 2020 Project. Along with this typification of the type of Nietneria, we provide important historical about original materials.